Efektivitas Intervensi Non-Farmakologis dalam Program Pengendalian Rokok pada Remaja: Sistematik Literatur Review - Mazaya, Betsy Elisse; Dolifah, Dewi; Rahmat, Delli Yuliana (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: The increase in cigarette consumption is not only among adults, but also among the younger generation. The health sector in Indonesia urgently needs to understand how policies and programs can be more effectively implemented to combat smoking among adolescents in Indonesia. Aims to identify interventions and important factors that facilitate successful smoking cessation in adolescents.Methods: A Systematic review, using Publish Or Perish databases (PubMed, Crossref, Google Scholar, Scopus, Semantic Scholar) and the COCHRANE Library. Selection was based on PICOTS, which included adolescents and young adults who had never smoked, had been exposed to tobacco smoke, had ever smoked, or were planning to quit. Non pharmacological intervention, RCT studies with a minimum duration of 6 weeks were published in English in 2019-2024.Results: Reported interventions were successful in strengthening tobacco-free behaviors, but the impact and scale of implementation were limited. Changes in knowledge, attitudes and behaviors, social support, policy and environment, satisfaction and participation, and program effectiveness play an important role in the success of the intervention. Interventions range from training, consultation, skills development, to collaboration using personalized and interactive content, and development of tobacco-free content on social media.Conclusion: The use of non pharmacological interventions has the potential to create tobacco-free behaviors in adolescents. It is important to differentiate between interventions for adolescent smokers and non-smokers in order to tailor the intervention to the content to be delivered.